2001
DOI: 10.1046/j.1365-2524.2001.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to healthcare access in a non-elderly urban poor American population

Abstract: An understanding of perceived barriers to health-care is critical to improving healthcare access for all Americans. To determine perceived barriers to health-care in an urban poor population in Dayton, Ohio, a face-to-face door-to-door survey of individuals identified through targeted, stratified, area probability sampling was done. A sample of 413 non-elderly poor adults, including 19% without telephones, reported personal relevance of various barriers to healthcare access. Most frequently endorsed barriers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 15 publications
3
86
0
5
Order By: Relevance
“…They are twice as likely as other workers to become unemployed, and consequently experience economic hardships (Corcoran & Hill, 1980). Poor workers and their families receive lower health care benefits due to access barriers (Ahmed, Lemkau, Nealeigh, & Mann, 2001;Guendelman, Wyn, & Tsai, 2002;Wolfe, 1994) and lower social security benefits upon retirement (Ozawa, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…They are twice as likely as other workers to become unemployed, and consequently experience economic hardships (Corcoran & Hill, 1980). Poor workers and their families receive lower health care benefits due to access barriers (Ahmed, Lemkau, Nealeigh, & Mann, 2001;Guendelman, Wyn, & Tsai, 2002;Wolfe, 1994) and lower social security benefits upon retirement (Ozawa, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional analysis used 2015 data from the Behavioral Risk Factor Surveillance System (BRFSS) conducted by the Center for Disease Control [18]. BRFSS collects data in the United States and U.S territories by conducting telephone surveys with Random Digit Dialing (RDD) techniques for landline and mobile phones concerning chronic health conditions, health-related risk behaviors, and use of preventive services for participants 18 years and older.…”
Section: Designmentioning
confidence: 99%
“…These states were chosen for their higher proportions of individuals who reported (a) fair or poor general health, (b) having no healthcare coverage, (c) difficulty with cost and paying for healthcare, and (d) being middle-aged females based on the BRFSS 2015 prevalence survey data maps [18].…”
Section: Samplementioning
confidence: 99%
“…Although lack of education and insurance benefits may play a small part in these statistics, the working poor report more barriers to accessing preventative care and are less likely to receive care than those living above the poverty line [3,4]. Sadly, Bloch et al [5] also found that primary care providers "lack…understanding of the lived reality of poverty" and have "prejudicial attitudes" which lead to "a failure to collect adequate data about patients' social circumstances and to the development of inappropriate plans of care" (p. 1).…”
Section: Introductionmentioning
confidence: 99%